Pumped Up by the Cold: Elemental Quotas and Stoichiometry of Cold-Water Diatoms - Lomas, Michael W.; Baer, Steven E.; Acton, Sydney; Krause, Jeffrey W. (Frontiers in Marine Science, 2019)
Phytoplankton cellular elemental quotas are important for evaluating the coupling of nutrient cycles and assessing nutrient limitation in the ocean. While cell element quotas have been shown to vary in response to growth conditions (e.g., light, nutrient supply), an overriding trait is cell size and biovolume. Allometric relationships are lacking data for phytoplankton grown under polar temperature conditions (e.g., <5oC); limited field data using single-cell stoichiometry measurements have shown polar diatoms may have significantly different allometry versus low-latitude counterparts. In this study, 11 strains of diatoms isolated from sub/polar waters (both Arctic and Antarctic) were grown in batch growth mode. Cellular carbon (C), nitrogen (N), phosphorus (P), silica (Si), cell number and biovolume were measured during mid-exponential and early stationary growth phases. An allometric log-log relationship was observed between cell element quotas and biovolume, although the strain Odontella aurita was consistently an outlier. Including O. aurita resulted in regression slopes for C, N, P and Si that were lower than values from the reviewed literature of temperate organisms; excluding O. aurita resulted in regression slopes that were more similar to published values for each element. However, the intercepts of the elemental quotas in the allometric relationships ranged from ~5-fold to ~100-fold greater than published values depending upon the element and the growth phase, meaning that the elemental density is significantly higher for diatoms grown at cold temperatures, although the physiological mechanism(s) cannot be resolved in this study. Cellular ratios of C, N, and P were consistent with prior research, but clearly showed the importance of taxonomic variability as all strains of the genus Thalassiosira behaved more similarly to each other than to the other diatom strains tested. Si:C ratios, in contrast, for non-Thalassiosira strains were greater and approached values commonly observed for iron-limited cells. These results show that a different set of allometric scaling equations is needed when considering sub/polar diatoms relative to temperate and tropical diatoms, which will impact regional and global model parameterization. In addition, these results highlight the role of phytoplankton diversity on biogeochemistry, even within the closely aligned families of diatoms.